Adsorption Analysis of Fluoride Removal Using Graphene Oxide/Eggshell Adsorbent - Norhusna Mohamad Nor; Nur Hidayahtul Nazrah Kamil; Amirul Izan Mansor; Hawaiah Imam Maarof (Universitas Gadjah Mada, 2020)
Graphene oxide with eggshells (GO/ES) adsorbent has been studied for fluoride ions (F–) removal. An adsorption study was conducted in batch experiments at different adsorption parameters, which are initial F– concentration, contact time, and temperature. The effects of these adsorption parameters towards F– removal by using GO/ES adsorbent were investigated. The adsorption parameters were then analyzed with adsorption isotherms (Langmuir and Freundlich), kinetics (pseudo-first-order and second-order) and thermodynamic studies. Under various parameters, GO/ES is proven as an effective adsorbent with an adsorption capacity of F– are up to 48 mg/g. The experimental data were satisfactorily fitted with Langmuir isotherm, which illustrated the monolayer pattern of F– adsorption into GO/ES adsorbent. The adsorption kinetic analysis indicated that the adsorption data could be well described by Pseudo-second-order kinetic model, which indicated the chemisorption process, while thermodynamic studies revealed that the adsorption of F– was an exothermic process.